2019
DOI: 10.1002/pssr.201800466
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Two‐Dimensional Topological Materials: CdX (X = F, Cl, Br, and I)

Abstract: Two‐dimensional (2D) transition‐metal halides have attracted great interest owing to their versatile applications in electronics, optoelectronics, and renewable energy storage/conversions. Using first‐principles calculations, it is proposed that a new series of 2D transition‐metal halide CdX (X = F, Cl, Br, and I) monolayers with honeycomb lattice structure show topological properties. When omitting the spin–orbital coupling (SOC) effect, all of them behave as Dirac semimetal whose Fermi surface is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The CdF band structure shows semimetallic character, with Dirac-like linear dispersive bands above (≈0.25 eV) the Fermi energy at the K point in the BZ, with a small local gap of around 100 meV is opening up in the presence of SOC, ensures the massive Dirac nature. At the Γ point near the Fermi energy parabolic band dispersion, originating from the Cd-5s orbitals, which is consistent with the reported results [59]. On the other side, the CrI 3 band structure shows, as mentioned in the literature, the large global gap of around 1 eV near Fermi energy, with magnetic moment 3.0 µ B /f.u, where the In the band structure of CrI 3 -CdF heterostructures shown in figure 3, we observed few interesting generic features in all the heterostructures.…”
Section: Electronic Band Structuressupporting
confidence: 93%
See 3 more Smart Citations
“…The CdF band structure shows semimetallic character, with Dirac-like linear dispersive bands above (≈0.25 eV) the Fermi energy at the K point in the BZ, with a small local gap of around 100 meV is opening up in the presence of SOC, ensures the massive Dirac nature. At the Γ point near the Fermi energy parabolic band dispersion, originating from the Cd-5s orbitals, which is consistent with the reported results [59]. On the other side, the CrI 3 band structure shows, as mentioned in the literature, the large global gap of around 1 eV near Fermi energy, with magnetic moment 3.0 µ B /f.u, where the In the band structure of CrI 3 -CdF heterostructures shown in figure 3, we observed few interesting generic features in all the heterostructures.…”
Section: Electronic Band Structuressupporting
confidence: 93%
“…For that, we have calculated the Fermi velocity for all the heterostructures. We found that the Fermi velocities are similar order of magnitude (≈10 6 m s −1 ) to that of the isolated CdF mono-layer system [59], even in the heterostructure systems with the presence of magnetic interactions. We have calculated the ratio of Fermi velocities in heterostructure systems with respect to the isolated CdF Fermi velocity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Notably, novel topological materials within the 2D MX family have been addressed in a few recent reports. [44][45][46][47][48] We emphasize that the physics underlying the formation of Dirac cones in the family of group-II MX compounds identified in our study differs fundamentally from the work of Zhou et al [44], which focuses on transition-metal compounds with band edges that are constructed via localized d electrons. Dirac cone in Cd-based MX compounds, Yi et al [45] attributed the Dirac cones they found to the interaction between the metal s-and anion-p states, which does not reflect the actual orbital interaction in these compounds.…”
mentioning
confidence: 63%